نظرية النظم لعبد القاهر الجرجاني ودورها في إثراء اللغة وكشف المعنى - حسني, نور الهدى (Revues faculté des lettres et des langues, 2017)
ملخــــــص:      تهدف هذه الدراسة إلى  تحديد مفهوم النظم عند عبد القاهر الجرجاني،  والبحث في كيفية ظهور المصطلح وكيفية تحقّقه، وتوضيح مدى إسهام نظرية في إثراء اللغة  وضبط المعنى، من خلال ما تطرحه من أدوات لغوية ووجوه للتراكيب بينها فروق لغوية في أداء المعنى،كشف عنها الجرجاني وهو يبيّن إعجاز القرآن الكريم من خلال صياغته وتراكيبه، كما تتناول الدراسة بالتحليل  والمقارنة بعض تقاطعات نظرية النظم في سياق تحليلها لإعجاز القرآن الكريم مع الدراسات اللسانية الحديثة                   Abstract: Abd  Elkahir  El  Djordjani’s  Theory  of  Nadm  and  Its  Role  in  Enriching  the  Language  and  Uncovering  Meaning The  aim  of  this  study  is   to   determine  the  concept  of  Nadm  in  Ebd  Elkahir  El  Djordjani,  to   look  at  how  the  term  has  emerged  and  how  it  is  achieved,  and  to   clarify  the  extent  to  which  a  theory  has  contributed  in  the  enrichment  of   the  language  and  in  the   adjustment  of  meaning  through  what  it  poses  from   linguistic  tools  and  forms  of   strutures  which  have  language  differences  in  rendering  meaning,  whereby  El  Djordjani  has  disclosed  them  when  he  shows  the  Holy  Quran  Miracle  through  its  formulation  and  structure.  The  study  also  addresses  through  analysis  and  comparison  some  of  the  intersections  in  the  theory  of  Nadm  in  the  context  of  its  analysis  of  the  Holy  Quran  Miracle  with  modern  linguistic  analysis.